Influence of Stress on Electronic and Optical Properties of Rocksalt and Wurtzite MgO–ZnO Nanocomposites with Varying Concentrations of Magnesium and Zinc - Yin-Pai Lin; Sergei Piskunov; Laima Trinkler; Mitch Ming-Chi Chou; Liuwen Chang (Nanomaterials, 2022)
The structural, electronic and optical properties of stressed MgO–ZnO nanocomposite alloys with concentrations of Zn and Mg varying from 0.125 to 0.875 were studied using ab initio simulations. Two crystal structures are considered for the initial MgO–ZnO alloys: the rocksalt Mg<semantics>1−x</semantics>Zn<semantics>x</semantics>O and wurtzite Zn<semantics>1−x</semantics>Mg<semantics>x</semantics>O phases. For rocksalt Mg<semantics>1−x</semantics>Zn<semantics>x</semantics>O, the optimized structures are stable at pressures below 10 GPa. The larger the Mg concentration and pressure, the wider the <semantics>Eg</semantics> of the rocksalt phase. In contrast, the optimal geometries of wurtzite Zn<semantics>1−x</semantics>Mg<semantics>x</semantics>O reveal a diversity of possibilities, including rocksalt, wurtzite and mixed phases. These effects lead to the fact that the optical properties of wurtzite Zn<semantics>1−x</semantics>Mg<semantics>x</semantics>O not only demonstrate the properties of the wurtzite phase but also indicate the optical features of the rocksalt phase. In addition, mixed phases of Zn<semantics>1−x</semantics>Mg<semantics>x</semantics>O simultaneously provide the characteristics of both wurtzite and rocksalt phases with the same structures in different dielectric matrices.